PEMBUATAN APLIKASI PENCATATAN KEUANGAN DAN MASTER DATA PRODUK BERBASIS DESKTOP UNTUK PROGRAM DIGITALISASI PADA KEDAI LIBONG COFFEE - Adi Fitrianto; Dwiyanjana Santyo Nugroho; Felisianus Novandri Rahmat; I Gusti Ayu Agung Aristi Putri (LPPM Universitas Bina Bangsa, 2023)
Currently, digitalization has become a crucial requirement in running a small and medium-sized enterprise (UMKM) business. Digitalization has been widely implemented in the operational processes of UMKMs, such as financial recording, inventory management, work management, payments, reservations, customer service, marketing, and even auditing processes. Libong Coffee is a coffee shop from Flores that sells coffee products made from raw materials sourced from Flores. Located on Senen Raya Street in Central Jakarta, Libong Coffee has gained a significant number of customers. Libong Coffee has great potential for growth, but unfortunately, not all operational activities at Libong Coffee are digitalized. Therefore, in this project, our focus is on developing an application with main features of financial data recording and product master data to support the ongoing digitalization program at Libong Coffee. The programming method used in developing this application is the Model View Controller (MVC) model. MVC is a technique that separates code into several components: Model, View, and Controller. Each part has its own functions, and by using this method, it provides additional benefits to application developers. The outcome of this project is an application for Libong Coffee with main features including financial data recording and product master data. This application is expected to assist Libong Coffee in achieving its digitalization goals